2023
DOI: 10.3389/fphys.2023.1210107
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical fitness and musculoskeletal health in firefighters

Abstract: Introduction: Firefighters are often placed in situations that require high levels of physical exertion, leading to significant strain on firefighters’ musculoskeletal system, predisposing them to musculoskeletal discomfort (MSD) and/or musculoskeletal injury (MSI). Physical fitness programs are often recommended and justified, in part, to prevent injuries. The aim of this study was to determine the association between physical fitness and musculoskeletal health (MSH) in firefighters.Methods: A total of 308 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…While also ensuring that they are educated on the benefits of opting for healthier diets while on-or off-duty. In addition, implementing minimum requirements for cardiorespiratory fitness, and muscular strength and endurance are necessary to ensure that firefighters are physically capable of performing their duties (33,80). This will also help maintain good CVH in firefighters to ensure that they are not at risk for CVD-related events while on duty (4, 81).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While also ensuring that they are educated on the benefits of opting for healthier diets while on-or off-duty. In addition, implementing minimum requirements for cardiorespiratory fitness, and muscular strength and endurance are necessary to ensure that firefighters are physically capable of performing their duties (33,80). This will also help maintain good CVH in firefighters to ensure that they are not at risk for CVD-related events while on duty (4, 81).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the well-known intense physical requirements of firefighting, many firefighters do not maintain the appropriate levels of physical conditioning that are required for peak performance at work (29,31,32). However, studies have shown that firefighters, particularly in the CoCTFRS, that are overworked are predisposed to musculoskeletal injuries and musculoskeletal discomfort (30,33).…”
Section: Introductionmentioning
confidence: 99%
“…These activities increase physiological demands and maximal heart rates, potentially leading to cardiovascular strain [6]. Research affirms that for firefighters to manage those job stressors and reduce the possibility of musculoskeletal injuries, they should maintain high levels of cardiovascular health, muscular strength, and endurance [7,8]. Concurrently, research indicates that performance of occupational tasks is positively associated with abdominal strength, upper body endurance (as measured by push-ups), upper body strength (via one repetition of max bench press), and power (as assessed by a step test) [9,10].…”
Section: Introductionmentioning
confidence: 99%